2009
DOI: 10.2105/ajph.2007.130278
|View full text |Cite
|
Sign up to set email alerts
|

The Scientific Basis for Law as a Public Health Tool

Abstract: Systematic reviews are generating valuable scientific knowledge about the impact of public health laws, but this knowledge is not readily accessible to policy makers. We identified 65 systematic reviews of studies on the effectiveness of 52 public health laws: 27 of those laws were found effective, 23 had insufficient evidence to judge effectiveness, 1 was harmful, and 1 was found to be ineffective. This is a valuable, scientific foundation-that uses the highest relevant standard of evidence-for the role of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…Black and Latino children did not show significant benefit from legislation mandating BPB use and disparities in use widened. Expanding research on interventional public health laws is critical as more states use injury prevention legislation to improve BPB use rates 24. Analysis of appropriate child passenger restraint use, with a focus on proper use, is vital to determine if all children are benefitting from the passage of injury prevention legislation.…”
Section: Discussionmentioning
confidence: 99%
“…Black and Latino children did not show significant benefit from legislation mandating BPB use and disparities in use widened. Expanding research on interventional public health laws is critical as more states use injury prevention legislation to improve BPB use rates 24. Analysis of appropriate child passenger restraint use, with a focus on proper use, is vital to determine if all children are benefitting from the passage of injury prevention legislation.…”
Section: Discussionmentioning
confidence: 99%
“…We found few studies and none indicating negative health effects of civil rights laws or rulings. 2 Public health law studies have largely focused on laws explicitly addressing public health, and, published literature has not examined the effects of civil rights laws and their enforcement (Moulton et al, 2009; Gostin, Wiley & Frieden, 2015). While our hypothesis that the public health benefits of the implementation of civil rights laws can be large and long term probably applies to several racial and ethnic minority populations, most of the studies we found examined effects on black populations.…”
Section: Effects Of Civil Rights Law and Enforcement On The Health Ofmentioning
confidence: 99%
“…It is important to assess the results of specific legislative measures; researchers are already making concerted efforts to study the impact of laws on public health. 22 Early evaluations of novel approaches in the US and elsewhere can help identify strengths and weaknesses, and promising interventions can be adapted to Canada's social and cultural context.…”
Section: Potential Roadblocksmentioning
confidence: 99%